This would be 10-2 which would equal 8
Answer:
Step-by-step explanation:
x-y=7
-3x+9y=-39
Divide the second equation by 3
-x +3y = -13
Add this to the first equation
x-y=7
-x +3y = -13
----------------------
0x +2y = -6
Divide by 2
2y/2 = -6/2
y = -3
Now find x
x-y = 7
x -(-3) = 7
x+3 = 7
Subtract 3 from each side
x = 4
(4,-3)
Or by substitution
x-y=7
solve for x
x = 7+y
-3x+9y=-39
Substitute y+7 in for x
-3(7+y) +9y = -39
Distribute
-21 -3y +9y = -39
Combine like terms
-21 +6y = -39
Add 21 to each side
6y = -18
Answer:
brainliest plz
Step-by-step explanation:
Answer:
A Irrational
Step-by-step explanation:
We have that
<span>x + 8.6 = 36.2
step 1
</span><span>Subtract 8.6 both members
</span><span>x+8.6-8.6=36.2-8.6
x=27.6
the answer is
the solution is x=27.6
</span>